(untitled) (Research Journal, 2024)
This paper aims to assess the decision-making position of elected women of local bodies of Ilam Municipality. The study attempts to explore whatever women’s position has changed as expects in household decision making, participation in local development women rights and empowerment and in socio-economic condition after the new constitution and declaration of Nepal as Republications state. The researcher and has selected 15 households and semi structure interviews and quasi-experimental methods was adopted for the data collections. The study is based on the qualitative nature of data and the major findings were drawn that women’s position in decision making has changed in terms of women’s rights, participation in socio-economic and political sectors and women empowerment as compared in the past socio-economic structure of the male dominated society. The research findings indicated that women at local bodies have both challenges and opportunities and there is high potential that they can gradually transfer the existing patriarchal frameworks through education, awareness, involvement and empowerment.